Engaging in co-creation experiences: The role of affective image and satisfaction - Islam, M. R.; Loureiro, S. M. C.; Carvalho, I.; Ramires, A. (Journal of Hospitality and Tourism Insights, 2025)
Purpose This study proposes a conceptual model and aims (1) to understand how co-creation experience influences guest engagement, (2) to analyse the effect of satisfaction and affective image between co-creation experience and guest engagement, and (3) to analyse the effect of guest engagement on behavioural intentions. Design/methodology/approach A questionnaire-based online survey was conducted targeting U.S.-based hotel customers. Developed on Qualtrics and distributed via Mechanical Turk, the survey garnered 465 useable responses from individuals who had visited international chain hotels within the last year. Data analysis was performed using Structural Equation Modelling (SEM) in IBM SPSS Amos. Findings The findings revealed significant direct effects of co-creation experience on affective image and guest satisfaction, with guest satisfaction notably influencing guest engagement, and guest engagement directly influencing behavioural intention. However, both co-creation experience and affective image showed minimal direct impact on guest engagement. The study also highlighted the importance of indirect effects and total effects in understanding the dynamics between the constructs analysed. Research limitations/implications The findings revealed significant direct effects of co-creation experience on affective image, with affective image notably influencing guest engagement, and guest engagement directly influencing behavioural intention. Although satisfaction had direct effects on guest engagement, co-creation experience showed minimal direct impact on guest satisfaction and on guest engagement. Practical implications This study advises managers to use co-creation primarily to enrich guest experiences and establish emotional connections rather than as a tool for directly enhancing engagement. It recommends that managers invest in strategies to enhance guest engagement beyond co-creation given the direct link between guest engagement and behavioural intentions, and the minimal direct impact between co-creation, guest engagement and satisfaction. Originality/value This study demonstrates that affective image is a pivotal mediator between co-creation experience and guest engagement. The findings provide valuable implications for hospitality practitioners in designing and managing co-creation experiences, emphasizing the importance of fostering a positive affective image in the value co-creation process to attain positive behavioural outcomes.